Research trend of functional magnetic resonance imaging in diabetes mellitus research: a visualization and bibliometric analysis - Zongbo Sun; Yuanyuan Li; Xueli Qu; Luguang Wang; Shengyin Zhu; Xuejing Sun; Li Yang; Xiaonan Sun (Frontiers in Neurology)
BackgroundUnderstanding the neurological complications associated with diabetes mellitus is essential for developing comprehensive treatment strategies. Functional magnetic resonance imaging (fMRI) is a powerful tool for investigating brain functional and structural changes associated with various conditions, including diabetes mellitus.ObjectivesTo analyze the application trends, research hotspots, and emerging frontiers of fMRI in diabetes mellitus research through a comprehensive bibliometric analysis.MethodsA systematic literature search was conducted utilizing the Web of Science Core Collection (WoSCC) database. Bibliometric tools, including VOSviewer (version 1.6.20), CiteSpace (version 6.3.R1), and R (version 4.3.3), were employed for data analysis.ResultsA total of 706 articles about fMRI and diabetes mellitus were published from 1987 to 2024. The United States of America (USA) ranks first (n = 931), followed by China (n = 756) and Germany (n = 270) regarding total publications. Harvard University ranks first in terms of total publications. Among the top ten institutions regarding publications, the majority of articles originated from the USA. The journal Diabetes has the highest number of publications. The author SHAO YI ranks first in total publications, while FRITSCHE ANDREAS ranks first in total citations. The top five keywords identified are “dementia,” “risk,” “brain,” “Alzheimer’s disease,” and “functional connectivity.” Keyword burst analysis indicates that the recent research hotspots included “impairment,” “dysfunction,” and “diagnosis.”ConclusionCognitive impairment and dysfunction related to diabetes mellitus, along with Alzheimer’s disease and dementia, and their diagnosis were identified as focal areas of research. Future investigations should concentrate on predicting and early diagnosing cognitive function in patients with diabetes mellitus using fMRI. The findings of this study provide a valuable reference for researchers and clinicians seeking to explore the neurological dimensions of diabetes mellitus and develop targeted therapeutic approaches.